EI24 alleviates renal interstitial fibrosis through inhibition of epithelial‐mesenchymal transition and fibroblast activation. Issue 1 (24th December 2020) - Mao, Yanwen; Zhang, Xiaohuan; Peng, Wei; Liu, Huiming; Zhou, Xingchen; Liang, Luqun; Xiang, Jiayi; Zhang, Huifang; Wang, Dan; Liu, Lingling; Zhou, Yuxia; Zhang, Fan; et al.
Abstract: Etoposide‐induced 2.4 (EI24) exerts tumor suppressor activity through participating in cell apoptosis, autophagy, and inflammation. However, its role in renal diseases has not been elucidated. This study showed that the EI24 level decreased gradually in the kidneys of mice with unilateral ureteral obstruction (UUO) and in another fibrosis model induced by diabetic kidney disease. The overexpression of EI24 was used to investigate the possible role both in vivo and in vitro. The overexpression 1 day after UUO through tail vein injection alleviated the progression of renal interstitial fibrosis (RIF). EI24 inhibited epithelial‐mesenchymal transition, excessive deposition of the extracellular matrix, and activation of fibroblasts. Furthermore, administration of EI24‐overexpressing plasmids restrained the phosphorylation of nuclear factor‐κB (NF‐κB) and c‐Jun kinase (JNK) through regulating the proteasome‐dependent degradation of TRAF2, and then, inhibited the expression of downstream inflammation‐associated cytokines (interleukin‐6, tumor necrosis factor‐α, and monocyte chemotactic protein‐1) and infiltration of macrophages and neutrophils in mouse kidney after UUO. In conclusion, the data indicated that EI24, a novel anti‐fibrosis regulator, was important in the progression of RIF.